Eveil des femmes paysannes pour le développement communautaire dans la région de Lwiro, Sud-Kivu, Zaïre - Mambo Bashi-Mulenda, M. (Tropicultura, 1995)
Awakening of Country-Women of the Community Development in Lwiro Region, South Kivu- Zaire (. Thirty-five country-women of Lwiro region and its surroundings (South-Kivu, Zaire) exploiting two goggy zones for agricultural activity, have taken up an initiative to gather themselves into an association named "Comite des Mamans Bika". This association aims to allow these women to act efficaciously their true role as village development adresses in the improvement of nutritional condition of population and especially in the feeding of ill-nourished children sent to the Pediatric Hospital of Lwiro. In spite of multiple difficultes of organisation, planification and management they often meet in their communitary exploitation linked to the lack of production parameters control, their agricultural yield presents an annual increasing mean rate valued to 38 %.